TURN-TAKING STRATEGIES IN CONVERSATION BY WILL SMITH AND ELLEN TALK SHOW ON YOUTUBE CHANNEL - Agustinus Alwin Tango; Afriana Afriana (IKIP Siliwangi, 2024)
Conversation analysis focuses on how different people handle their ordinary conversational experiences. This study's aim was to determine the different turn-taking methods used by Ellen and Will Smith on their YouTube channel, The Ellen Show. The researchers applied Stenstrom's hypothesis. This idea distinguishes three categories. Specifically, taking the turn (starting up, taking over, interrupting), holding the turn (Filled pause and verbal filled, silent pause, lexical repetition), and yielding the turn (prompting, appealing, and giving up). The researchers used a qualitative approach to describe the turn- taking strategies that included in the conversation, In this study, researcher used document or content analysis as a type of content research analytical research methods, because the data or content of this research is in the form of videos words and sentences spoken from the Will Smith Full Interview with Ellen on the The Ellen Show YouTube Channel. The result showed there are several types found in the conversation such as: starting with the most dominant taking the turn (clean start 1, Link 1, uptakes 1, alert 3, metacomments 5), holding the turn (Silent pause 2, filled pause 1, repitition 1). and there is no Data of yielding the turn.